2017
DOI: 10.1007/jhep02(2017)055
|View full text |Cite
|
Sign up to set email alerts
|

Deconfinement, chiral transition and localisation in a QCD-like model

Abstract: Abstract:We study the problems of deconfinement, chiral symmetry restoration and localisation of the low Dirac eigenmodes in a toy model of QCD, namely unimproved staggered fermions on lattices of temporal extension N T = 4. This model displays a genuine deconfining and chirally-restoring first-order phase transition at some critical value of the gauge coupling. Our results indicate that the onset of localisation of the lowest Dirac eigenmodes takes place at the same critical coupling where the system undergoe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 70 publications
6
31
1
Order By: Relevance
“…The mobility edge, λ c , vanishes at a temperature compatible with T c [16], suggesting that localisation of the low Dirac modes is closely related to deconfinement and chiral restoration. This is further supported by a similar coincidence of the three phenomena in other theories and models, like SU(3) pure gauge theory in 3+1 dimensions [22], the N f = 3 unimproved staggered fermion model mentioned above [23], and also in a toy model for QCD [24], devised in Ref.…”
Section: Contentssupporting
confidence: 72%
See 2 more Smart Citations
“…The mobility edge, λ c , vanishes at a temperature compatible with T c [16], suggesting that localisation of the low Dirac modes is closely related to deconfinement and chiral restoration. This is further supported by a similar coincidence of the three phenomena in other theories and models, like SU(3) pure gauge theory in 3+1 dimensions [22], the N f = 3 unimproved staggered fermion model mentioned above [23], and also in a toy model for QCD [24], devised in Ref.…”
Section: Contentssupporting
confidence: 72%
“…The mobility edge, λ c , vanishes at a temperature compatible with T c [16], suggesting that localisation of the low Dirac modes is closely related to deconfinement and chiral restoration. This is further supported by a similar coincidence of the three phenomena in other theories and models, like SU(3) pure gauge theory in 3+1 dimensions [22], the N f = 3 unimproved staggered fermion model mentioned above [23], and also in a toy model for QCD [24], devised in Ref.[25] precisely to study the issue of localisation.A qualitative understanding of the relation between deconfinement and localisation is provided by what in this paper will be referred to as the "sea/islands" picture of localisation [26,27]. The idea is that the local Polyakov lines provide a sort of local potential for the Dirac modes via the effective boundary condition that they impose on the eigenmodes.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The interested reader can find a full description of our methodology and results in the published paper [1]. Analogous investigations were reported at this conference [6] and in recent papers [7,8].…”
Section: Introductionsupporting
confidence: 53%
“…This system possesses a genuine phase transition in the thermodynamic limit, as the spatial box size goes to infinity while the temporal size is kept fixed at N t = 4 [9]. Here it was shown that the disappearance of localized modes at the low-end of the Dirac spectrum precisely coincides with the chiral phase transition [10]. However, the chiral phase transition of N t = 4 staggered quarks does not survive in the continuum limit.…”
Section: Introductionmentioning
confidence: 88%